A new family of metallaboratrane complexes based on 7-azaindole: B-H activation mediated by carbon monoxide - Tsoureas, Nikolaos; Haddow, Mairi F.; Hamilton, Alex; Owen, Gareth R. (Chemical Communications, 2009)
The reaction of Ir(COD)(Tai) [where Tai = {HB(7-azaindoyl) 3}-] with carbon monoxide results, via a sequence of hydride migration and insertion steps, in the formation of the first complexes to contain a metal-to-boron dative interaction supported by 7-azaindole units. © The Royal Society of Chemistry 2009.